Influence of minimally invasive endodontic access cavities and bonding status of resin composites on the mechanical property of endodontically-treated teeth: A finite element study. Issue 2 (February 2022) - Lin, Fei; Ordinola-Zapata, Ronald; Fok, Alex S.L.; Lee, Roy
Abstract: Objective: To study the mechanical behavior of endodontically-treated teeth with minimally invasive endodontic access cavities and resin composite restorations under different bonding conditions using finite element analysis (FEA). Methods: Four Class-II endodontic access cavities including the mesio-occlusal minimally-invasive (MO-MIE), mesio-occlusal conventional (MO-CONV), disto-occlusal minimally-invasive (DO-MIE), and disto-occlusal conventional (DO-CONV) cavities were prepared in 3D-printed maxillary first molars. Each tooth was subjected to root canal preparation and scanned using micro-CT to provide a 3D structural model which was virtually restored with resin composite. An intact 3D-printed molar was used as control. FEA was conducted under a 250-N vertical load. Three different interfacial bonding conditions between dentin/enamel and resin composite were considered, i.e. fully bonded, partially debonded, and fully debonded. The maximum principal stress of dentin and the normal tensile stress at the interfaces were recorded. The risk factor of failure for each component was then calculated. Results: In the fully-bonded tooth, the dentin-composite interface showed significantly higher stress and a higher risk factor than dentin, indicating that debonding at the dentin-composite interface would occur prior to dentin fracture. With the dentin-composite interface debonded, the enamel-composite interface exhibited higher stress and a higher risk factor than dentin, indicating that debonding at the enamel-composite interface would occur next, also prior to dentin fracture. With the resin composite fully debonded from the tooth, stress in dentin increased significantly. Irrespective of the bonding status, the CONV groups exhibited higher median stresses in dentin than the MIE groups. Significance: Within the limitation of this study, it was shown that debonding of the resin composite restoration increased the stress in dentin and hence the risk of dentin fracture in endodontically-restored teeth. Minimally-invasive access cavities could better safeguard the fracture resistance of interproximally-restored teeth compared to conventional ones.